Nailfold capillary patterns in ballgame and endurance athletes - Otsuki, Takeshi; Suwabe, Kazuya; Yoshikawa, Toru; Kotani, Kiwamu; Zempo-Miyaki, Asako (Frontiers in Physiology, 2025)
PurposeNailfold capillary patterns can be observed noninvasively using light microscopy. Nailfold capillaries are straight, U-shaped, and densely looped in healthy individuals and may be altered by disease or lifestyle factors, such as diet. However, the effects of daily physical activity and exercise training on nailfold capillary patterns remain unclear. This study aimed to examine the effects of exercise training on nailfold capillary patterns by investigating these patterns in endurance athletes, ballgame athletes, and sedentary healthy men.MethodsFive healthy men participated in nailfold capillary pattern measurements on three consecutive days to test the reproducibility and bilateral differences in the nailfold capillary loop density, length, and width measured using light microscopy and a commercial analysis system. The nailfold capillaries of 10 endurance athletes (endurance group; eight long-distance runners and two triathletes), 10 ballgame athletes (ballgame group; seven soccer players and three basketball players), and nine sedentary healthy men (sedentary group) were then examined using light microscopy.ResultsThe day-to-day coefficient of variation for the nailfold capillary loop density, length, and width were 4.9% ± 1.6%, 7.5% ± 1.3%, and 4.2% ± 1.5%, respectively. No significant differences in these measurements were observed between the dominant and non-dominant hands. Nailfold capillary density was greater in the ballgame group than in the endurance and sedentary groups. Capillary loop length was shorter in the ballgame group than in the endurance and sedentary groups. No significant differences in capillary loop density and length were observed between the endurance and sedentary groups. No significant intergroup differences were observed in capillary loop width.ConclusionThese results suggest that the nailfold capillary patterns of male ballgame athletes differ from those of endurance athletes and sedentary healthy men. Ballgame training may affect nailfold capillary patterns in sedentary healthy men.